2006
DOI: 10.1111/j.1349-7006.2006.00378.x
|View full text |Cite
|
Sign up to set email alerts
|

The recombinant kringle domain of urokinase plasminogen activator inhibits in vivo malignant glioma growth

Abstract: In a previous report, the recombinant kringle domain (UK1) of the urokinase type plasminogen activator (uPA) showed antiangiogenic activity. Here, we investigated in vivo antitumor effects of the UK1 of human uPA employing a brain tumor model. The systemic administration of UK1 purified from pichia expression (10 and 50 mg/kg/day intraperitoneally for 25 days) led to suppress the growth of a U87 human glioma xenograft, implanted into the brains of male BALB/cSlc nude mice, by 35% and 80%, respectively. In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…Our results also show that simultaneous downregulation of uPAR and uPA suppressed angiogenin, a proangiogenic molecule. Recently, researchers have shown that the recombinant kringle domain (UK1) of uPA had antiangiogenic activity by causing the suppression of various proangiogenic molecules, including angiogenin, in glioma cells (35). Our results confirm the previous findings that interference with the uPAR-uPA system retards angiogenesis.…”
Section: Discussionsupporting
confidence: 90%
“…Our results also show that simultaneous downregulation of uPAR and uPA suppressed angiogenin, a proangiogenic molecule. Recently, researchers have shown that the recombinant kringle domain (UK1) of uPA had antiangiogenic activity by causing the suppression of various proangiogenic molecules, including angiogenin, in glioma cells (35). Our results confirm the previous findings that interference with the uPAR-uPA system retards angiogenesis.…”
Section: Discussionsupporting
confidence: 90%
“…6B). Previous studies by Kim CK and collegues [31] have shown that the recombinant kringle domain of ATF inhibits glioma invasion in vivo . To check if uPA ATF, which includes the GFD and the kringle domain, plays a role in angiogenin expression and secretion, we first treated endothelial cells with different concentrations of ruPA for 24 hrs, then treated with ruPA ATF, and assayed for angiogenin expression by western blotting and angiogenin secretion by ELISA.…”
Section: Resultsmentioning
confidence: 94%
“…Kim et al [31] have shown that UK1, the recombinant kringle domain of urokinase plasminogen activator, shows anti-angiogenic activity. In their study, they demonstrated that systemic administration of UK1 (50 mg/kg) suppressed U87 tumor growth in vivo by 80%.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we have shown that the recombinant kringle domain of urokinase (UK1) is a potent angiogenesis inhibitor and it inhibits tumor growth in a brain tumor model [ 18 , 19 ]. However, potential problems such as poor bioavailability, antigenicity and inconsistency in bioactivity from batch to batch during production of recombinant protein can hamper the application of UK1 to clinical practice [ 20 ].…”
Section: Introductionmentioning
confidence: 99%